2014
DOI: 10.1186/1471-2431-14-194
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in severely injured children: experiences of a German level 1 trauma center (2002 – 2011)

Abstract: BackgroundTrauma in pediatric patients is a major cause of death. This study investigated differences between decedents and survivors. Furthermore, an analysis of preventable and potential preventable trauma deaths was conducted and errors in the acute trauma care were investigated.MethodsAll patients aged less than 16 years with an Injury Severity Score (ISS) ≥ 16 upon primary admission to the hospital between July 2002 and December 2011 were included in this study. Decedents were compared with survivors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 31 publications
4
33
0
Order By: Relevance
“…7 This study showed that the mean of Hb among patients is 11.6±2.77, another study performed by Schoeneberg C et al, which showed that the mean of HB among patients was 10.6±1.8. 13 This study showed that the mean of Hct on arrival is 33.0 , another study performed by Ciarallo L et al, in a retrospective review conducted on 257 patient, that the mean hematocrit (Hct) was 35.2% on arrival. 14 Regarding the blood transfused to the polytraumatised pediatric patients, 90% of the injured children did not need any blood transfusion, 10% (6 patients) of the polytraumatised children needed blood transfusion when Hct < 30% and this matches the data of Ciarallo L et al, Patients who present with a Hct <30%, or who have polytraumatic injuries had a relatively greater risk of needing a transfusion.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…7 This study showed that the mean of Hb among patients is 11.6±2.77, another study performed by Schoeneberg C et al, which showed that the mean of HB among patients was 10.6±1.8. 13 This study showed that the mean of Hct on arrival is 33.0 , another study performed by Ciarallo L et al, in a retrospective review conducted on 257 patient, that the mean hematocrit (Hct) was 35.2% on arrival. 14 Regarding the blood transfused to the polytraumatised pediatric patients, 90% of the injured children did not need any blood transfusion, 10% (6 patients) of the polytraumatised children needed blood transfusion when Hct < 30% and this matches the data of Ciarallo L et al, Patients who present with a Hct <30%, or who have polytraumatic injuries had a relatively greater risk of needing a transfusion.…”
mentioning
confidence: 72%
“…The study showed that the range of respiratory rate was . According to GCS, this study showed that 67% of the patients have GCS of (13)(14)(15). According to investigations, the mean of Hb among patients is 11.6±2.77.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This particularity is likely of a multifactorial determinism. Most likely, technological development favored the dissemination of information and increased therapeutic possibilities for the pediatric patient, although the currently available data on the treatment of severely traumatized pediatric patients is extremely limited (5).…”
Section: Discussionmentioning
confidence: 99%
“…However, trauma is among the most important causes of mortality and morbidity in children (0-16 years) (5). A particular and attention-worthy aspect of trauma in children is suspected child abuse, especially in those aged 0-12 months, this particular group being under-tested and often neglected in comparison with those presenting to the physician following accidents or other injuries (6).…”
Section: Introductionmentioning
confidence: 99%